Latin American algorithm for treatment of relapsing-remitting multiple sclerosis using disease-modifying agents - Alessandro Finkelsztejn; Alberto Alain Gabbai; Yara Dadalti Fragoso; Adriana Carrá; Miguel Angel Macías-Islas; Raul Arcega-Revilla; Juan García-Bonitto; Carlos Luis Oehninger-Gatti; Geraldine Orozco-Escobar; Adriana Tarulla; Fernando Vergara; Darwin Vizcarra (Arquivos de Neuro-Psiquiatria, 2012)
OBJECTIVE: It is estimated that circa 50,000 individuals have relapsing-remitting multiple sclerosis in Latin America. European and North-American algorithms for the treatment of multiple sclerosis do not foresee our regional difficulties and the access of patients to treatment. METHODS: The Latin American Multiple Sclerosis Forum is an independent and supra-institutional group of experts that has assessed the latest scientific evidence regarding efficacy and safety of disease-modifying treatments. Accesses to treatment and pharmacovigilance programs for each of the eight countries represented at the Forum were also analyzed. RESULTS: A specific set of guidelines based upon evidence-based recommendations was designed for Latin America. Future perspectives of multiple sclerosis treatment were also discussed. CONCLUSIONS: The present paper translated an effort from representatives of eight countries discussing a matter that cannot be adapted to our region directly from purely European and North-American guidelines for treatment.